Gondwana Paleolandscapes: Long-Term Landscape Evolution, Genesis, Distribution and Age - Rabassa, Jorge Oscar (2010)
The concept of “Gondwana Landscape” was defined by Fairbridge (1968) as an “ancestral landscape” composed of “series of once-planed remnants” that “record traces of older planation” episodes, during the “late Mesozoic (locally Jurassic or Cretaceous)”. This has been called the “Gondwana cyclic land surface” in the continents of the southern hemisphere, occurring extensively in Australia, Southern Africa and the cratonic areas of South America. Remnants of these surfaces are found also in India, in the northern hemisphere and it is assumed they have been preserved in Eastern Antarctica, underneath the Antarctic ice sheet which covers that region with an average thickness of 3,000 meters. These paleolandscapes were generated when the former Gondwana super-continent was still in place and similar tectonic conditions in its drifted fragments have allowed their preservation. Remnants of equivalent surfaces, though of very fragmentary condition, have been described in Europe and the United States. These Gondwana planation surfaces are characteristic of cratonic regions, which have survived in the landscape without being covered by marine sediments over extremely long periods, having been exposed to long-term sub-aerial weathering and denudation. Their genesis is related to extremely humid and warm paleoclimates of “hyper-tropical” nature, with permanently water saturated soils, or perhaps extreme paleo-monsoonal climates, with seasonal and long term cyclic fluctuations, from extremely wet to extremely dry. Deep chemical weathering is the dominant geomorphological process, with the development of extremely deep weathering profiles, perhaps of up to many hundreds of meters deep. The weathering products are clays, kaolinite, pure quartz and other silica form sands, elimination of all other minerals and duricrust formation, such as ferricretes (iron), silcretes (silica) and calcretes (calcium carbonate). Annual precipitation in these periods would have been higher than 10,000 mm, with extremely high, mean annual temperatures, such as 25-30 ºC. This can be achieved only under extremely stable tectonic and climatic conditions. The geomorphological processes included extensive pediplanation under wet/semiarid and/or seasonally changing climates. Finally, their evolution continued with fluvial removal of the weathering products in wet climates and with hydro-eolian deflation in the areas with semiarid environments or strong climatic seasonality. The final landform products of these deep weathering/pediplanation systems are planation surfaces, inselbergs, bornhardts, duricrust remnants covering tablelands, associated pediments, granite weathered landscape, etc. Some concepts relating of these ancient landform systems were theoretically developed by Walther Penck in the early 20th century. The Gondwana paleolandscapes were studied by Alexander Du Toit and Lester C. King in Africa, and more recently, by Timothy Partridge and Rodney Maud in South Africa, C. Rowland Twidale and Cliff Ollier in Australia and Lester C. King and João José Bigarella in Brazil, among many others. Both in Australia and Southern Africa these landform systems have been identified as formed in the middle to late Jurassic, throughout the Cretaceous and, in some cases, extending into the Paleogene, when Gondwana was still only partially dismembered.